AND 2021
DOI: 10.20517/and.2021.06
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among norepinephrine, NOX2, and neuroinflammation: key players in Parkinson’s disease and prime targets for therapies

Abstract: Aim: No studies have examined whether interactions between the apolipoprotein E4 (ApoE4) allele and peripheral biomarkers, hypertension, and type 2 diabetes mellitus (T2DM) may impact the neurocognitive, behavioral, and social dysfunctions in amnestic mild cognitive impairment (aMCI) and Alzheimer's disease (AD). We aimed to clinically define and biologically validate a subgroup of aMCI subjects who take up an intermediate position between controls and AD patients. Methods:In 61 healthy controls, 60 subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Nurr1, also known as NR4A2/NOT/TINUR, is a member of the orphan nuclear receptor family 4 (NR4A), necessary for the mdDA neurons’ development, maturation, and functional maintenance [ 46 , 69 , 70 ]. It is also involved in neuroprotection and neuroinflammation regulation by inhibiting pro-inflammatory factors in microglial and astrocytes cells [ 71 , 72 , 73 ]. Notably, in mdDA neurons, the decreased levels of Nurr1 were characterized during aging, which may be related to the increased morbidity of PD [ 74 , 75 ].…”
Section: Tfs In Dopamine Cell Therapymentioning
confidence: 99%
“…Nurr1, also known as NR4A2/NOT/TINUR, is a member of the orphan nuclear receptor family 4 (NR4A), necessary for the mdDA neurons’ development, maturation, and functional maintenance [ 46 , 69 , 70 ]. It is also involved in neuroprotection and neuroinflammation regulation by inhibiting pro-inflammatory factors in microglial and astrocytes cells [ 71 , 72 , 73 ]. Notably, in mdDA neurons, the decreased levels of Nurr1 were characterized during aging, which may be related to the increased morbidity of PD [ 74 , 75 ].…”
Section: Tfs In Dopamine Cell Therapymentioning
confidence: 99%
“…In a cohort study, Villumsen et al [50] found individuals troubled with IBD are more susceptible to PD. Inflammation is a well-known feature of PD [51]. It has been proposed that this inflammation may be triggered by a disruption in the intestinal barrier, which exposes the system to inflammatory microbial compounds such LPS, a component of bacterial cell walls [52].…”
Section: Intestinal Inflammation May Promote Progression Of Synuclein...mentioning
confidence: 99%
“…Under inflammatory or neurotoxic conditions, glia generally turns into a harmful phenotype accompanied by the release of EVs, contributing to the increase of DAergic neuron vulnerability and the exacerbation of neuronal death ( Wang et al, 2021 ). Results from the α-synuclein overexpression mouse model indicate that the abnormity accumulated α-synuclein can alter the pro-inflammatory gene expression profile in the glial.…”
Section: Role Of Glia-derived Extracellular Vesicles In Neurodegenerative Diseasesmentioning
confidence: 99%